Cover Picture: Metal‐organic framework‐based cancer theranostic nanoplatforms (View 2/2020). Issue 2 (26th June 2020) - Yang, Jie; Yang, Ying‐Wei
Abstract : In article number 20, Ying‐Wei Yang and co‐workers describe metal‐organic framework (MOF)‐based theranostic nanoplatforms that integrate various imaging technologies and treatment strategies have been extensively investigated to improve the diagnosis and treatment of cancer. In this cover, a MOF‐loaded carriage dragged by two horses (one horse represents imaging technologies and the other means treatment strategies) is transported to the castle, symbolizing that MOFs as multifunctional theranostic tools could deliver cargos to the tumor sites for precise cancer therapy guided by various imaging technologies.